2007
DOI: 10.1159/000099462
|View full text |Cite
|
Sign up to set email alerts
|

Totally Implantable Access Ports: Approach via Femoral Vein

Abstract: The purpose of this study was to report our results of totally implantable access ports (TIAP) approached via the femoral vein. Patients and Methods: Seven patients were enrolled. The mean age was 62 years. Four patients were male, and 3 patients were female. Six patients received TIAP via the right femoral vein and 1 patient via the left femoral vein. All patients underwent local anesthesia. The reason for femoral vein TIAP placement, mean operative time, follow-up time and complications were recorded. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The use of FICCs was first described in patients with mediastinal tumors, bilateral breast cancer, lung cancer with mediastinal infiltration, or lymphoma with SVC compression. 3,4,7 Traditionally, the inferior vena cava approach is performed through common femoral vein cannulation at the groin site. However, this approach, because of the exit site in the groin area, has an elevated risk of late catheter-related complications, in particular infection and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of FICCs was first described in patients with mediastinal tumors, bilateral breast cancer, lung cancer with mediastinal infiltration, or lymphoma with SVC compression. 3,4,7 Traditionally, the inferior vena cava approach is performed through common femoral vein cannulation at the groin site. However, this approach, because of the exit site in the groin area, has an elevated risk of late catheter-related complications, in particular infection and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…the femoral vein and placement of the catheter tip in the inferior vena cava (IVC) or at the IVC/RA 3,4 : such type of central access may be defined as FICC (femorally inserted central catheter).…”
Section: Ultrasound-guided Cannulation Of the Superficial Femoral Vei...mentioning
confidence: 99%
See 1 more Smart Citation
“…The femoral approach in critically ill patients has been shown to have a significantly higher infection rate than the SCV or the jugular vein approach in prospective studies [16]. A potential risk of infection should be discussed because the port implantation site is close to the groin [11]; thus, the port site should be placed as far away from the groin region as possible to avoid infection. Infection rates have been reported to be between 0% and 5% [15,[17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Although the IJV, SCV, and external jugular vein (EJV) [8] have been used for secondary access, several studies have suggested that both the SCV and the IJV should be avoided due to the high incidence of procedural complications, as well as central stenosis and thrombosis [5][6][7]9]. The risk of such complications is increased in patients undergoing hemodialysis, as well as in those with a history of multiple central venous catheterizations, bilateral breast cancer, infected tissue, or postradiogenic dermatitis of cutaneous metastasis [6,[9][10][11]. In such cases, the femoral vein (FV) approach could be considered an alternative method for TIVAP implantation, with the port implanted in the anterior abdominal wall, the anteroinferior thoracic wall or the anterior thigh [12,13].…”
Section: Introductionmentioning
confidence: 99%